Situating Scandinavian Poetry in the Computational Network Environment - Rustad, Hans Kristian Strandstuen (Poetry in the Digital Age, 2023)
This book investigates how Scandinavian poetry works in the context of digital media from a historical and theoretical perspective. How do digital media intervene in poetic form? How do they remediate older forms of poetry? And how can digital and digitalized poetry, which tends to be particularly self-reflexive, in turn shed light on the workings of digital technology?